Studi Kepemimpinan Kelurahan; Gaya Kepemimpinan Lurah Tondo - Sussanti Sussanti; Husen Husen (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2020)
This research concerning leadership style of headman of Tondo in Sub district of Mantilulore in Palu. Problems encountered in Tondo Region that was one of busiest village office in Palu, need definite style to optimize village office management. This research applied descriptive qualitative. Used primary data and secondary data, with indepth interview technique and documentation. Informant that involved in this research are 5 that chosen by using purposive sampling. Based on the research, that the style of leadership in village office of Tondo categorized the instruction runs well in managing government officials. The task implementation and responsible of government apparatus’ works, that need to be concern based on headman instruction.